037 Frontotemporal dementia or frontal variant alzheimer's disease? A case series. (29th July 2019) - Powell, Alice; Foxe, David; Halliday, Glenda M; Piguet, Olivier; Hodges, John R; Burrell, James R
Abstract : Introduction: Accurate prediction of the underlying neuropathology in behavioural variant frontotemporal dementia (bvFTD) is essential for future targeted therapy trials and prognostication. Alzheimer's disease (AD) pathology has been reported in a significant proportion of patients with clinical bvFTD. We sought to determine whether detailed clinical and neuroradiological assessment was sufficient to distinguish bvFTD with AD pathology from bvFTD with frontotemporal lobar degeneration (FTLD). Methods: Two patients with clinically diagnosed probable bvFTD but AD pathology at autopsy, were identified. The clinical, neuropsychological and imaging features of these patients were compared with those of ten patients with clinically probable bvFTD and proven FTLD pathology (tau, TDP-43, FUS). Results: Both patients with AD pathology presented with behavioural symptoms typical of bvFTD as well as memory impairment. Executive function, memory and visuospatial skills were impaired in both pathologic groups. Language skills were relatively spared in those with AD pathology. Neuropsychiatric symptoms were frequent in both groups but significant depression and anxiety were seen only in those with FTLD pathology. Dementia severity and caregiver burden were similar. The degree or topographical distribution of atrophy on MRI did not differ. Conclusions: Alzheimer's pathology may cause bvFTD symptoms which are otherwise indistinguishable to those caused by FTLD pathology. While there may be subtle differences in patterns of cognitive deficits, standard neuropsychological testing is insufficient to discern the underlying pathology. Similarly, structural imaging cannot be used to reliably identify AD pathology. Better access to amyloid biomarkers may be needed to more accurately define bvFTD caused by AD pathology.